Hubungan Kadar Estradiol Serum dengan Densitas Tulang pada Wanita Perimenopause dan Pascamenopause - , Arif Sulistiyo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Objective: To understand the correlation between serum estradiol levels with bone density status and using estradiol serum as a predictor of osteoporosis in perimenopausal and postmenopausal women. Method: An observational study with cross sectional design of 54 perimenopausal and postmenopausal women aged over 45 years conducted in June-August 2010 in RSUP dr. Sardjito Yogyakarta. Pearson correlation statistical test was used to determine the correlation between serum estradiol levels with bone density. Categorical variables were compared by using Chi-square test, whereas continuous variables were analyzed by One Way Anova and Student t-test. To assess the serum estradiol levels as a predictor of osteoporosis, Receiver Operator Curve (ROC) was used. Result: There was a significant positive correlation between serum estradiol levels with bone density status (score of Bone Mineral Density / BMD) (r = 0.456, p = 0.001). Bone density is also influenced by age, Body Mass Index (BMI), and menopausal status (p <0.05), whereas physical activity, fracture history, smoking, consumption of coffee, milk, calcium supplements, and steroids had no effect in this study (p> 0.05). ROC test produce an Area Under Curve (AUC) of 86.32%. Cut-off point (threshold value) of estradiol as a predictor of osteopenia / osteoporosis is 18.31 with a sensitivity of 94.12% and specificity of 70%. Conclusion: Serum estradiol levels and bone density status is positively correlated and can be used as a predictor of osteopenia/osteoporosis